Controllable Supramolecular Architectures for Modulating Optical Properties on the Molecular Aggregation Level. Issue 23 (4th July 2014) - Jiang, Runsheng; Xue, Zheng; Li, Yongjun; Qin, Zhihong; Li, Yuliang; Zhu, Daoben
Abstract: Driven by the association of chemical weak forces and solvent effects, zero‐ to two‐dimensional nanostructures of thiophene‐substituted perylene bisimide such as spheres and blocky structures were obtained. Light‐controlled intramolecular charge transfer from the trithiophene unit to the perylene bisimide in the solid state can induce a hypochromatic shift and enhanced fluorescent emission. Abstract : Light‐controlled intramolecular charge transfer from the trithiophene unit to the perylene bisimide in the solid state can induce a hypochromatic shift and enhanced fluorescent emission.